21ST CENTURY REPRESENTATIONS OF THE HOLOCAUST IN BRITAIN: AN EXAMINATION OF HOLOCAUST EXHIBITIONS AT THE IMPERIAL WAR MUSEUM LONDON AND JEWISH MUSEUM LONDON - NURUL AQILAH BINTE MOHD KHIRASHID (2020)
Master's